Analisis kesulitan menulis teks deskripsi pada peserta didik kelas IV sekolah dasar - Zulfa Astri Lutfiah; Rukayah Rukayah; Siti Kamsiyati (Universitas Sebelas Maret, 2021)
The purpose of this study was to describe the difficulty of writing descriptive texts in 4D grade students of SD Djama'atul Ichwan in the 2020/2021 school year. Writing descriptive text is one of the goals to be achieved in Indonesian language learning. This study will describe the difficulty of writing students' descriptive texts based on indicators from the modification of Dalman (2016:103) and Rukayah (2013:117). The method used in this research is descriptive qualitative using a case study approach. Taking research subjects using purposive sampling technique. The data source of this research was the 4D class students which consisted of six students as the research sample. The data collection technique was done by observing, interviewing, testing, and studying the documentation. The validity test of the data used in this study were technical triangulation and source triangulation. Data were analyzed using data analysis model Miles and Huberma. The results of this study indicate that students only master the title indicators in line with the theme. Students have not mastered other indicators, namely: 1) The content of ideas is in accordance with the title and involves the senses; 2) Cohesive and coherensive paragraphs; 3) Choice of words (diction); and 4) Spelling and punctuation. The results of this study provide insight into forms of difficulty in writing descriptive texts. The results of this study also encourage teachers to determine effective strategies, models, methods, and media so that they can overcome difficulties in writing descriptive texts.